2022
DOI: 10.1155/2022/4140022
|View full text |Cite|
|
Sign up to set email alerts
|

Multivariate Analysis of Recurrence after Hysteroscopic Diagnosis and Treatment of Endometrial Polyps following IVF-ET Failure

Abstract: Objective. To explore the risk factors affecting the recurrence of endometrial polyps (EPs) after hysteroscopic diagnosis and treatment of EPs following in vitro fertilization-embryo transfer (IVF-ET) failure by multivariate analysis. Methods. The clinical data of 369 patients with EPs hysteroscopically treated in our department due to IVF-ET failure from January 2017 to January 2020 were retrospectively analyzed, including the number and size of polyps, postoperative treatment, endometriosis (EM), hydrosalpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%